Leveraging Building Material as Part of the In‐Plane Robotic Kinematic System for Collective Construction. Issue 24 (24th June 2022) - Leder, Samuel; Kim, HyunGyu; Oguz, Ozgur Salih; Kubail Kalousdian, Nicolas; Hartmann, Valentin Noah; Menges, Achim; Toussaint, Marc; Sitti, Metin
Abstract: Although collective robotic construction systems are beginning to showcase how multi‐robot systems can contribute to building construction by efficiently building low‐cost, sustainable structures, the majority of research utilizes non‐structural or highly customized materials. A modular collective robotic construction system based on a robotic actuator, which leverages timber struts for the assembly of architectural artifacts as well as part of the robot body for locomotion is presented. The system is co‐designed for in‐plane assembly from an architectural, robotic, and computer science perspective in order to integrate the various hardware and software constraints into a single workflow. The system is tested using five representative physical scenarios. These proof‐of‐concept demonstrations showcase three tasks required for construction assembly: the ability of the system to locomote, dynamically change the topology of connecting robotic actuators and timber struts, and collaborate to transport timber struts. As such, the groundwork for a future autonomous collective robotic construction system that could address collective construction assembly and even further increase the flexibility of on‐site construction robots through its modularity is laid. Abstract : In this article, a co‐designed collective robotic construction system based on robotic actuators that leverage timber struts as part of the kinematic system is investigated. A comprehensive workflow for deploying the system based on research from the robot hardware design, task and motion planning (TAMP), computational design and monitoring perspectives is realized to detail out the application of such a system to build structures in‐plane.